QUANTITATIVE ABUNDANCE OF DENITRIFYING BACTERIAL DIVERSITY IN RELATION TO ABIOTIC FACTORS OF TOTAL NITROGEN AND ORGANIC CARBON IN THE SEDIMENTS OF RAJAKKAMANGALAM ESTUARY OF SOUTHWEST COAST OF INDIA - MOHIDEEN ASKAR NAWAS, P; JAWAHAR ALI. A (International Journal of Pharma and Bio Sciences, 2014)
An investigation was made on the diversity of aerobic heterotrophic denitrifying bacterial population in the sediment samples of six sampling stations (S-I to S-VI) at Rajakkamangalam estuary of southwest coast of India for the period of two years from January 2005 to December 2006. The result indicated that the distribution of denitrifying bacterial populations in the estuarine environment fluctuated much between sampling stations. Among the total denitrifying bacterial populations Pseudomonas was found to dominant group. The percentage of total denitrifying bacterial populations was low in the pollutant mixed stations.